"The tip of the iceberg": Commentary on sports, health inequity, and trauma exacerbated by COVID-19 - Noel-London, K. C.; Grimsley, C.; Porter, J.; Breitbach, A. P. (Journal of Athletic Training, 2020)
Objective: To discuss the relevance of system-level health inequities and their interplay with race in sports and athletic training, particularly during and after the coronavirus disease 2019 (COVID-19) pandemic.